MATING TYPES, METALAXYL RESISTANCE AND RACIAL COMPLEXITY IN PHYTOPHTHORA INFESTANS POPULATION-PRESENT SCENARIO - Singh, P. H.; Singh, B. P.; Bhat, M Narayana (Potato Journal, 2013)
Results of the studies revealed that A2 mating type continued to remain dominant in hilly areas while A1 was still dominant in sub-tropical plains. Resistance to metalaxyl had crossed the threshold level at most of the places studied. Frequency of 11 gene complex race 1.2.3.4.5.6.7.8.9.10.11 was highest at all the places.